2020
DOI: 10.1101/2020.06.23.168252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The SARS-CoV-2 receptor, Angiotensin converting enzyme 2 (ACE2) is required for human endometrial stromal cell decidualization

Abstract: 29 STUDY QUESTION 30Is SARS-CoV-2 receptor, angiotensin-converting enzyme 2 (ACE 2) expressed in the human 31 endometrium during the menstrual cycle, and does it participate in endometrial decidualization? 32 SUMMARY ANSWER 33 ACE2 protein is highly expressed in human endometrial stromal cells during the secretory phase 34 and is essential for human endometrial stromal cell decidualization. 35 WHAT IS KNOWN ALREADY 36ACE2 is expressed in numerous human tissues including the lungs, heart, intestine, kidneys and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Studies on animal models have described weak expression of ACE2 in endometrial cells of pregnant rats [ 29 ]. Expression of ACE2 in human endometrial cells in pregnancy is not described yet; however, first reports on ACE2 expression in the endometrium are currently being published [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on animal models have described weak expression of ACE2 in endometrial cells of pregnant rats [ 29 ]. Expression of ACE2 in human endometrial cells in pregnancy is not described yet; however, first reports on ACE2 expression in the endometrium are currently being published [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that SARS-CoV-2 uses ACE2 as a receptor for cellular entry and TMPRSS2 protease for viral Spike protein priming (25,26). The intestinal enterocytes have a higher expression of ACE2 compared to alveolar epithelial type II cells (27)(28)(29). Among the tested three cell lines in this work, ACE2 and TMPRSS2 were expressed at the highest level in Caco-2 cells (Fig.…”
Section: Sars-cov-2 Infection In the Intestine-on-chipmentioning
confidence: 69%
“…Consistent with these previous studies, our findings in the current case showed a close association between symptoms, positive RT‐PCR test results and the menstruation. This phenomenon might be partly explained by the findings of Chadchan et al 16 They found that the expression of angiotensin converting enzyme 2 (ACE2), by which SARS‐CoV‐2 enters human cells, is high in human endometrial stroma and increases in the secretory phase. Furthermore, ACE2 expression in human endometrial stroma is promoted by progesterone.…”
Section: Discussionmentioning
confidence: 99%